2022
DOI: 10.1038/s41388-022-02460-1
|View full text |Cite
|
Sign up to set email alerts
|

ISCA2 inhibition decreases HIF and induces ferroptosis in clear cell renal carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC), the most common form of kidney cancer, is typically initiated by inactivation of the von Hippel Lindau (VHL) gene, which results in the constitutive activation of the hypoxia inducible factors, HIF-1α and HIF-2α. Using a high throughput screen, we identify novel compounds that decrease HIF-1/2α levels and induce ferroptosis by targeting Iron Sulfur Cluster Assembly 2 (ISCA2), a component of the late mitochondrial Iron Sulfur Cluster (L-ISC) assembly complex. ISCA2 inhib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…It was also reported that HIF-1α and HIF-2α have different targets: HIF-1α regulates most of the glycolytic-related genes, whereas HIF-2α selectively regulates many iron-regulatory genes [ 175 , 176 ]. Consistently, the abovementioned studies showed that HIF-2α inhibits ferroptosis through its direct targets involved in iron metabolism, such as FTMT , in both tumor and normal cells [ 102 , 112 ]. However, it is also reported that HIF-1α regulates iron metabolism directly through transcriptionally regulation of its targets, such as TFRC and DMT1 [ 120 ], as well as indirectly through some other targets, such as CA9 [ 103 ].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It was also reported that HIF-1α and HIF-2α have different targets: HIF-1α regulates most of the glycolytic-related genes, whereas HIF-2α selectively regulates many iron-regulatory genes [ 175 , 176 ]. Consistently, the abovementioned studies showed that HIF-2α inhibits ferroptosis through its direct targets involved in iron metabolism, such as FTMT , in both tumor and normal cells [ 102 , 112 ]. However, it is also reported that HIF-1α regulates iron metabolism directly through transcriptionally regulation of its targets, such as TFRC and DMT1 [ 120 ], as well as indirectly through some other targets, such as CA9 [ 103 ].…”
Section: Discussionmentioning
confidence: 63%
“…In clear cell renal cell carcinoma (ccRCC), both HIF-1α and HIF-2α are stabilized by VHL loss, leading to the decrease in ferroptosis sensitivity to erastin or BSO via fatty acid β-oxidation and mitochondrial ATP-synthesis [ 101 ]. A recent study on clear cell renal cell carcinoma showed that the iron sulfur cluster assembly 2 (ISCA2), a component of the late mitochondrial iron sulfur cluster assembly complex, was induced by hypoxia (1% O 2 ) to promote HIF-1α/HIF-2α translation, leading to the inhibition of iron overload and erastin- or RSL3-induced ferroptosis [ 102 ].…”
Section: The Mechanism and Regulation Of Ferroptosis Modulated By Hyp...mentioning
confidence: 99%
“…STEAP3 influences ferroptosis and RCC progression via the p53/xCT pathway [63]. Studies have demonstrated that suppression of ISCA2 reduces HIF and causes ferroptosis in ccRCC [127]. Kerimoglu et al [128] revealed that the cyst(e)inase-rapamycin combination caused ferroptosis in both in vitro and in vivo models of hereditary leiomyomatosis and RCC.…”
Section: Pharmacological Progress Of Ferroptosis In Kidney Diseasesmentioning
confidence: 99%
“…Despite the availability of multiple therapeutic strategies, it is still necessary to explore novel therapeutic approaches and tumor markers. Recent studies have shown that tumor cells are more sensitive to ferroptosis than normal cells, Frontiers in Genetics frontiersin.org particularly renal cancer cells (Yang et al, 2014;Zou et al, 2019;Green et al, 2022). Therefore, in-depth studies on the role of ferroptosis-associated ncRNAs in kidney cancer may be meaningful for the discovery of novel tumor diagnostic markers and potential therapeutic strategies (Zhang et al, 2019;Lei et al, 2022;Li et al, 2022;Zhu et al, 2022).…”
Section: Ferroptosis-associated Ncrnas and Kidney Cancermentioning
confidence: 99%